Academic Quality Assurance Policy (December 2009) - Public Affairs (University of Ghana, 2011)
The University’s commitment to the assurance of the quality of its academic programmes is broadly expressed in its mission statement. The mission of the University is to “develop world-class human resources and capabilities to meet national development needs and global challenges through quality teaching, learning, research, and knowledge dissemination.
University of Ghana Special Reporter
Academic Quality Assurance Policy
Keywords: Report; UG Policies; University of Ghana